1995
DOI: 10.1007/bf00220929
|View full text |Cite
|
Sign up to set email alerts
|

Mapping genetic factors controlling pollen viability in an interspecific cross in Helianthus sect. Helianthus

Abstract: Segregation of 48 genetic markers, including one CMS restorer gene, one morphological character gene, six isozymes and 40 RAPD loci, was scored in a backcross progeny of an interspecific hybrid H. argophyllusxH. annuus cv RHA274. A linkage map was generated taking into account segregation distortions for 11 of the 48 loci in the frame of two different models considering locus-pair segregation in the context of either independent selection pressures or non-equilibrated parental classes. The map consists of nine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
61
1
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(67 citation statements)
references
References 28 publications
3
61
1
1
Order By: Relevance
“…Both Whitkus (1998) and observed up to 50% distortion in interspecific hybrid crosses of plants where segregation distortion was presumed to be a consequence of hybridization between divergent genomes. Such postzygotic barriers typically manifest themselves in linkage maps of reciprocal hybrid crosses resulting from selection on the F 1 gametes or by selection on recombinant backcross (BC) zygotes (Li et al 1997;Kim and Rieseberg 1999), where the degree of segregation distortion appears to be correlated with increasing genetic divergence between parental lines (Zamir and Tadmor 1986;Quillet et al 1995;Grandillo and Tanksley 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Both Whitkus (1998) and observed up to 50% distortion in interspecific hybrid crosses of plants where segregation distortion was presumed to be a consequence of hybridization between divergent genomes. Such postzygotic barriers typically manifest themselves in linkage maps of reciprocal hybrid crosses resulting from selection on the F 1 gametes or by selection on recombinant backcross (BC) zygotes (Li et al 1997;Kim and Rieseberg 1999), where the degree of segregation distortion appears to be correlated with increasing genetic divergence between parental lines (Zamir and Tadmor 1986;Quillet et al 1995;Grandillo and Tanksley 1996).…”
Section: Discussionmentioning
confidence: 99%
“…ARG has also been identified as a possible source of favorable alleles for salt and drought tolerance (Richards 1992) and insect resistance (Rogers and Thompson 1980;Rogers et al 1982Rogers et al , 1987Sujatha and Lakshminarayana 2007). Crosses between ANN and ARG produce vigorous offspring with reduced pollen viability (F 1 = 5-50% viable, BC 1 = 24-97% viable) and chromosomal abnormalities (Heiser 1951;Chandler et al 1986;Quillet et al 1995), resulting in restricted introgression in experimental crossing programs. Cytological studies identified meiotic abnormalities (e.g., univalents, rod bivalents, and tetravalents) in the interspecific hybrids, indicating that ANN and ARG differ by at least two reciprocal translocations (Heiser 1951;Chandler et al 1986;Quillet et al 1995).…”
mentioning
confidence: 99%
“…Crosses between ANN and ARG produce vigorous offspring with reduced pollen viability (F 1 = 5-50% viable, BC 1 = 24-97% viable) and chromosomal abnormalities (Heiser 1951;Chandler et al 1986;Quillet et al 1995), resulting in restricted introgression in experimental crossing programs. Cytological studies identified meiotic abnormalities (e.g., univalents, rod bivalents, and tetravalents) in the interspecific hybrids, indicating that ANN and ARG differ by at least two reciprocal translocations (Heiser 1951;Chandler et al 1986;Quillet et al 1995). A recent comparative mapping study identified five nonreciprocal translocations and two inversions between ANN and ARG (Heesacker et al 2009); however, this analysis was based on an ARG map with just 299 markers (i.e., SSRs, indels, and SSCPs), of which only 131 were orthologous to loci that had been mapped in ANN.…”
mentioning
confidence: 99%
“…There have been several reports on the inheritance of isozyme loci in populations of both wild and cultivated sunflower (Kahler and Lay, 1985;Torres, 1983;Rieseberg et al, 1993 and1995;Quillet et al, 1995), and several pairs of loci have been found to be linked (Table IV ). Mestries et al (1998) were the first authors who reported the mapping of a number of isozyme loci onto a proprietary RFLP linkage map.…”
Section: Genetic Mappingmentioning
confidence: 99%